Characteristics, treatment and disease burden among stage 3-4 chronic kidney disease patients with and without type 2 diabetes in Finland during 2016-2022 - Metsärinne, Kaj; Bodegard, Johan; Toppila, Iiro; Uusi-Rauva, Kristiina; Frederiksen, Line Elmerdahl; Brinkmann, Satu (OXFORD UNIV PRESS, 2025)
Background: Real-world evidence on the management of chronic kidney disease (CKD) with and without type 2 diabetes (T2D) is limited. This study described the characteristics, treatment, and disease burdenin patients with stage 3-4 CKD with and without T2D in Finland.
Methods: This cohort study used data from primary and hospital care in five municipalities in Finland to identify adults with stage 3-4 CKD, defined as having either one estimated glomerular filtration rate (eGFR) measurement of 15-59 ml/min/1.73m2 followed by a second measurement taken >= 90 days apart, or a registered CKD diagnosis. Prevalence was determined on 31 December 2022, and a cohort of incident stage 3-4 CKD patients was followed from the first date fulfilling eligibility criteria since 01 January 2016 (index) until death or 31 December 2022, and analyzed by T2D status.
Results: The prevalence of stage 3-4 CKD was 6.3%. Among the 12 474 incident stage 3-4 CKD patients, the majority were non-T2D (73%). The median age was similar for non-T2D and T2D CKD patients, respectively. Baseline albuminuria screening was 9% among non-T2D and 53% among T2D. The use of kidney-protective treatments at index was also lower in non-T2D patients (47%), compared with T2D patients (69%). The use of kidney-protective treatments remained unchanged during 12 months after index. Healthcare resource utilization was high, and CKD or heart failure contributed considerably more to the all-cause healthcare costs than atherosclerotic diseases, regardless of T2D status. In both CKD subgroups, 10% had died within one year.
Conclusions: In Finland, CKD is highly prevalent and associated with high risks and low use of albuminuria testing and kidney-protective medications. Most CKD patients were non-T2D, which showed lower use of preventive management and similar risks compared with T2D patients. These findings call for an urgent need for improved awareness and risk management, especially in non-T2D CKD patients.